KONSEP KEADILAN SOSIAL DALAM PEMIKIRAN FAZLUR RAHMAN: IMPLIKASI TERHADAP HUKUM EKONOMI SYARIAH - Syukri M. Yusuf (An Nuqud Journal of Islamic Economics, 2025)
Social justice is one of the fundamental principles of Islamic teachings that is highly relevant to the development of contemporary Islamic economic law. Fazlur Rahman’s thought offers a progressive approach to understanding the normative values of the Qur’an through contextual interpretation, which places justice as the primary objective of Sharia. This article aims to analyze the concept of social justice in Fazlur Rahman’s thought and its implications for Islamic economic law. This study employs a qualitative method using a literature review approach, through an analysis of Fazlur Rahman’s works and related literature on Islamic economics. The results of the study indicate that the concept of social justice according to Fazlur Rahman is not merely understood as equitable economic distribution but also as an effort to create collective well-being through social reform, the elimination of exploitation, and the development of an economic system oriented toward human welfare. The implications of this line of thought for Islamic economic law are evident in the need to reinterpret Islamic economic norms to make them more responsive to modern challenges such as economic inequality, structural poverty, and market injustice. Thus, Fazlur Rahman’s approach makes a significant contribution to the development of Islamic economic law that is more substantive, adaptive, and oriented toward social justice.